ANALYSIS OF THE DUMPING OF ALUMINUM ZINC COATED STEEL FROM THE PERSPECTIVE OF MASLAHAH MURSALAH AL GHAZALI: (Report of the Indonesian Anti-Dumping Committee) - Niki Apionita; Tetty Marlina Tarigan (LP2M IAI Nazhatut Thullab Sampang, 2022)
rading system that sells goods in foreign markets at prices below normal prices. And this is something that is natural in trading. However, under certain conditions it can have a very bad impact on similar industries in the dumping destination country, so it needs to be prohibited. However, the things that are useful can also be felt by consumers, namely they can enjoy goods at price below the normal price. So the practice of dumping BJLAS can be related to Maslahah Mursalah according to Imam Al-Ghazali. The purpose of this study was to determine how the analysis of the practice of dumping BJLAS based on the perspective of Maslahah Mursalah according to Imam al-Ghazali. This research approach uses a normative juridical approach, this type of research data uses library research data. The result of his research show that the practice of dumping BJLAS is not in accordance with Maslahah Mursalah according to Imam Al-Ghazali, because dumping BJLAS does not meet the requirements of maslahah mursalah according to Imam Al-Ghazali, namely the requirement in the category of dharuriyah (basic needs). Conditions of certainty of a benefit provided and do not meet Islamic law. Keywords: Dumping, al-Maslahah al-Mursalah, Imam Al-Ghazali